Profil Progesteron sapi Perah Frisian Holstein dengan Pemberian Pemberian PGF2α pada Korpus Luteum Persisten - ERPRINANDA GALUH BERLIANA (Universitas Pendidikan Mandalika, 2026)
The aim of this study was to determine the profile of progesterone hormone in serum dairy cattle that experienced corpus luteum persisntent in KUD Tani Wilis, Sendang Tulungagung district. This study used 10 diary cows that experience CLP that had body score condition under 3 and ever had breeding at least one time or had normal oestrous cycle. This study had three times to got sample. First when the cow had diagnosed, second when oestrous and third when 21 day after artificial Insemination. The result of this study showed the average progesterone profile of corpus luteum persistent at the first, second and thid sampels are 7.085 ± 0.85 ng/ml, 0.592 ± 0.08 ng/ml and 14.120 ± 5.15 ng/ml. the average oestrus is 6.9 day and conception rate is 60%.